Trèves/Augusta Treverorum, cité des Trévires : les premiers temps de la ville - Jennifer Morscheiser-Niebergall (Gallia)
The birth of Trier, Augusta Treverorum, is usually linked to the building of the wooden bridge over the Moselle in 18-17 BC. A careful analysis of the finds linked to the earliest levels of the streets shows that the grid was apparently not laid out before the Haltern ceramic horizon, around the turn of the millennia. Although remains of human occupation prior to this period have been found, especially the camp on the Petrisberg, clearly linked to the Treveran revolt in 29 BC, the physical creation of the town must be chronologically separated from the dating of the bridge.